Analisis Pengaruh Hedonic Shopping Tendency Dan Visual merchandising Terhadap Impulse Buying Dengan Positive Emotion Sebagai Variabel Intervaning Pada Area Ladies Matahari Department Store Tunjungan Plaza Surabaya - Yanthi, Devi (Jurnal Strategi Pemasaran, 2014)
This research tried to determine what factors are causing consumers to do impulse buying in the area of ladies at Matahari Department Store. Variables examined in this research include hedonic shopping tendency and visual merchandising as the independent variable, positive emotion as the intervening variable, and impulse buying as the dependent variable. The sample used amounted 100 rerspondents. By using PLS-SEM analysis technique, demonstrated that through positive emotion variables, hedonic shopping tendency and visual merchandising effect on impulse buying.